Reševanje problemov mehanike tal - Jelušič, Primož (2021)
Solving Problems in Soil Mechanics. The objective of the book is to apply the laws of soil mechanics to practical examples. The objective of the book is to apply the laws of soil mechanics to practical examples. It presents the basic procedures for evaluating the physical and mechanical properties of soils, which are the basis for solving problems in geotechnical engineering. According to the existing literature in the field of soil mechanics, the contents of the book are divided into 16 chapters: Introduction, Soil Classification, Three-Components of Soil, Stresses in Soil, Stresses in Soil Layer, Darcy's Law, Soil Permeability, Groundwater Seepage, Stresses and Strains, One-Dimensional Compression, Consolidation, Creep, Shear Strength, Determination of Shear Strength Parameters, Elastic Stresses and Deformations, and Stability Analysis.
Keywords: Soil Mechanics; Soil Properties; Stresses in Soil Layer; Consolidation; Shear Strength; Stability Analysis